PENGEMBANGAN BAHAN AJAR BERBASIS FLIPPED CLASSROM PADA MATERI PIKTOGRAM SISWA FASE B SEKOLAH DASAR - Adam Baihaqi; Lala Qomara Putri; Mohamad Alfi Hikmatul Hakim; Muhammad Imadil Fathan Wahidien; Najma Aulia Hasna; Vivi Yuanitha; Andhin Dyas Fitriani (Afore : Jurnal Pendidikan Matematika, 2026)
This research aims to develop teaching materials based on the Flipped Classroom model for pictogram content in Phase B elementary school students. The study employed a design and development approach using the PPE model (Planning, Production, Evaluation). The planning stage involved analyzing learning outcomes and content; the production stage generated digital teaching materials designed using Canva and equipped with worksheets, instructional videos accessible via QR codes, and assessment rubrics; while the evaluation stage involved expert validation on material and design aspects. The validation results indicated that the teaching materials met the criteria of validity across all assessment components, making them suitable for classroom use. The developed materials support active, independent, and student-centered learning aligned with 21st-century learning demands. This study concludes that the Flipped Classroom model is effective for developing pictogram teaching materials and has the potential to enhance students’ conceptual understanding and learning autonomy.